Legal and tactical basis for conducting a search of a person’s residence or other property: identifying the ways to resolve the controversial issues - O. O. Kovalenko (Bulletin of Kharkiv National University of Internal Affairs)
A search of a person's residence or other property is one of the most typical and, at the same time, the most complex investigative ( search) actions. Its purpose is to identify, record factual data on the event of a criminal offence or related event, find and seize the instruments of a criminal offence, property acquired by illegal means or items excluded from use by law, as well as to establish the location of the wanted persons. This investigative (search) action is associated with the restriction of the rights of the person in whose residence or premises it is conducted, who may not even be involved in the commission of a criminal offence. For this reason, it is important to ensure that the search is conducted in compliance with a number of legal and organisational principles, as well as using a set of effective tactical techniques.